2018
DOI: 10.1111/jphp.13023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radix isatidis polysaccharide on alleviating insulin resistance in type 2 diabetes mellitus cells and rats

Abstract: Objectives The objective of this paper was to explore the effects of Radix isatidis polysaccharide (RIP) extracted from Radix isatis on alleviating insulin resistance. Methods The insulin resistance models of 3T3‐L1 preadipocytes and type 2 diabetic rats were established to evaluate the insulin resistance activity of RIP. Key findings Radix isatidis polysaccharide within the concentration range of 25–100 μg/ml could reduce cell supernatant glucose and TNF‐α levels (P < 0.01) and increase the expression of PI‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…21–24 Ye Yuan et al found that Radix isatidis polysaccharides reduced insulin resistance and improved glucose metabolism, lipid metabolism and oxidative stress. 25,26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21–24 Ye Yuan et al found that Radix isatidis polysaccharides reduced insulin resistance and improved glucose metabolism, lipid metabolism and oxidative stress. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Ye Yuan et al found that Radix isatidis polysaccharides reduced insulin resistance and improved glucose metabolism, lipid metabolism and oxidative stress. 25,26 In previous studies, EP showed antiviral activity at oral doses of 88 mg kg −1 d −1 and 176 mg kg −1 d −1 . 27 Xiaowei Huo et al used 125 mg kg −1 , 250 mg kg −1 and 500 mg kg −1 aqueous extracts from the seeds of O. violaceus (the main component of EP), orally administered to mice to investigate their hepatoprotective effects.…”
Section: Food and Function Papermentioning
confidence: 95%
“…and insulin (10 U/Kg, IP) as comparison standards. The safety evaluation was based on biochemical, hematological, and histopathological changes (Li et al, 2019). At the end of administration for the four weeks, rats were weighted, after fasting for 12 hr, and then, the blood samples were withdrawn from the retro-orbital plexus using heparinized micro-capillaries (Optilab, Berlin, Germany) under anesthesia (thiopental sodium 50 mg/kg, IP) (Gazdhar et al, 2013).…”
Section: Safety and Efficacy Evaluationmentioning
confidence: 99%
“…Hyperglycemia not only affects the transduction of apoptotic signals in islet cells but also damages tissues and organs [21]. As one of the major metabolic organs, the liver is the main organ damaged by diabetes.…”
Section: Effects Of Pagr On Histopathological Changes In Livermentioning
confidence: 99%